PENGARUH PROJECT BASED OUTDOOR LEARNING ACTIVITY MENGGUNAKAN MEDIA AUDIOVISUAL TERHADAP PERILAKU BELAJAR ANAK DI PAUD - Primayana, Kadek Hengki; Dewi, Putu Yulia Angga; Gunawan, I Gede Dharman (PRATAMA WIDYA : JURNAL PENDIDIKAN ANAK USIA DINI, 2020)
This study aims to determine the significant impact of Project Based Outdoor Learning Activity using audiovisual media on children's learning behavior in PAUD Cluster VI Buleleng District. The research design used is a quasi-experimental design and quantitative methods. The population of this research is the whole group B in Cluster VI of Buleleng District. The sample of this study is TK B group Aisyiyah Bustanul Athfal, with a total of 15 children, group B TK Dharma Suda Singaraja, with a total of 18 children. Use the t-test to analyze data. The results obtained are t arithmetic = 3.15, the significance level is 5%, and when dk = 31, t table = 2.04. Therefore, the value of the t count> t table is 3.15> 2.04. It can be concluded that Project-Based Outdoor Learning Activity using audiovisual media has an impact on children's learning behavior in PAUD Cluster VI Buleleng District.